Political Participation and Workplace Voice: The Spillover of Suppression by Supervisors. (May 2022) - Geurkink, Bram; Akkerman, Agnes; Sluiter, Roderick
This article aims to establish the connection between people's voice at work and their political voice. We theorize and model a spillover mechanism from supervisors' responses to workplace voice to political participation. Applying structural equation modeling on a unique dataset (N = 3129), we find that while support and suppression of workplace voice both affect political participation, they do so through different mechanisms. In addition, we find that supervisors' suppressive responses to employees' voice can trigger both positive and negative effects on different forms of political participation. Thereby, we contribute to the understanding of the link between participation at work and participation in politics.